Spatial Analysis of Instrumental Period (1900-2024) Earthquakes in Malatya and its Surroundings - Uysal, Ahmet; Sunkar, Murat; Avci, Vedat (Geomatik Journal, 2025)
This study examines the spatial analyses of earthquakes that occurred in Malatya and around during the instrumental period. Malatya is situated in the western part of the Eastern Anatolia Region, at the junction of the East Anatolian Fault Zone (EAFZ) and the Malatya Fault Zone (MFZ). The earthquakes that occurred in Kahramanmara & scedil; on February 6, 2023, along with the subsequent tremors, revealed that Malatya and its surroundings are among the most tectonically active areas in the region. Due to its tectonic features, the province has experienced destructive earthquakes during both the instrumental and historical periods. In the region, 13 earthquakes with a magnitude of 6 or higher occurred during the historical period, while 4 such earthquakes were recorded in the instrumental period. The most devastating among these were the Kahramanmara & scedil; earthquakes of February 6, 2023, with magnitudes of 7.7 and 7.6. The epicenter of the first earthquake was in Pazarc & imath;k (Kahramanmara & scedil;), while the second was centered in Ekinozu-Elbistan. The second earthquake caused greater destruction in Malatya and its surrounding settlements. Over 500 earthquakes with magnitudes of 4 or higher have occurred in and around Malatya during the instrumental period. Spatial and intensity analyses of earthquakes were conducted using data from these earthquakes and the active faults around Malatya. According to the analysis results using Geographic Information Systems (GIS), earthquake intensity was found to increase to the southwest and south of Malatya province. The fact that Malatya city and its major district centers are located in areas with high earthquake intensity highlights the significance of earthquake disaster.
Keywords: Malatya; East Anatolia Fault Zone; Seismicity; Spatial analysis